Organ specific gene expression in the regenerating tail of Macrostomum lignano. - Lengerer, B; Wunderer, J; Pjeta, R; Carta, G; Kao, D; Aboobaker, A; Beisel, C; Berezikov, E; Salvenmoser, W; Ladurner, P (Elsevier, 2017)
Temporal and spatial characterization of gene expression is a prerequisite for the understanding of cell-, tissue-, and organ-differentiation. In a multifaceted approach to investigate gene expression in the tail plate of the free-living marine flatworm Macrostomum lignano, we performed a posterior-region-specific in situ hybridization screen, RNA sequencing (RNA-seq) of regenerating animals, and functional analyses of selected tail-specific genes. The in situ screen revealed transcripts expressed in the antrum, cement glands, adhesive organs, prostate glands, rhabdite glands, and other tissues. Next we used RNA-seq to characterize temporal expression in the regenerating tail plate revealing a time restricted onset of both adhesive organs and copulatory apparatus regeneration. In addition, we identified three novel previously unannotated genes solely expressed in the regenerating stylet. RNA interference showed that these genes are required for the formation of not only the stylet but the whole male copulatory apparatus. RNAi treated animals lacked the stylet, vesicula granulorum, seminal vesicle, false seminal vesicle, and prostate glands, while the other tissues of the tail plate, such as adhesive organs regenerated normally. In summary, our findings provide a large resource of expression data during homeostasis and regeneration of the morphologically complex tail regeneration and pave the way for a better understanding of organogenesis in M. lignano.